Surkovian Narrative on the Future of Russia: Making Russia a World Leader - Makinen, Sirke (The journal of communist studies and transition politics, 2011)
Vladislav Surkov, the first deputy head of the Russian presidential administration and one of the key ideologists during Putin's presidency, offers an interesting insight into the Russian political elite and their narratives on Russia's past, present and future. The ultimate goal in the Surkovian narrative is to make Russia a leader in the world and guarantee the well-being of Russian citizens. Modernization should be understood as one of the main means in order to achieve this. The Surkovian narrative is strongly influenced by neo-liberal ideology and accordingly emphasizes the responsibility of citizens for their own well-being and happiness. However, Surkov assigns the state a stronger role than the conventional neo-liberal logic would suggest, thereby partly reproducing the former Russian and Soviet modernization discourses by stressing Russia's distinctive path to modernization.